Central nervous system germ cell tumor, an archetypal AYA tumor and a model for pediatric and neuro-oncology collaboration, review from the EURACAN domain 10 group - Faure Conter, Cecile; Calaminus, Gabriele; Nicholson, James; Idbaih, Ahmed; Hoang Xuan, Khê; Vasiljevic, Alexandre; Morana, Giovanni; Szathmari, Alexandru; Ajithkumar, Thankamma; Frappaz, Didier (Frontiers in Oncology, 2022)
Adolescents and young adults (AYA) with cancer are under-represented in clinical trials and have thus not benefited from the same improvement in outcomes as either younger or older patients. Central nervous system germ cell tumors (CNS-GCT) represent an ideal model of AYA tumor as their incidence peaks during adolescence and young adulthood. Since the early 90’s, SIOP (International Society of Pediatric Oncology) has launched two successive European trials: SIOP CNS-GCT96 (January 1996 to December 2005) and SIOP CNS-GCTII protocols (October 2011 to July 2018), for CNS-GCTs. With the removal of the upper age limit in the SIOP CNS-GCTII trial, and closer collaboration between pediatric and adult oncologists within AYA multidisciplinary tumor boards, the proportion of adults enrolled in France has dramatically increased over time. The current article will use the example of CNS-GCT to illustrate how to build a bridge between pediatric and adult oncology, how this can apply to other types of brain tumors and discuss ways to promote cancer care in the AYA population.